Adverse pathology and undetectable ultrasensitive prostate‐specific antigen after radical prostatectomy: is adjuvant radiation warranted?. (23rd June 2015) - Simon, Ross M.; Howard, Lauren E.; Freedland, Stephen J.; Aronson, William J.; Terris, Martha K.; Kane, Christopher J.; Amling, Christopher L.; Cooperberg, Matthew R.; Vidal, Adriana C.
Abstract : Objectives: To determine if men with adverse pathology but undetectable ultrasensitive (<0.01 ng/mL) PSA are at high‐risk for biochemical recurrence (BCR), or if there is a subset of patients at low‐risk for whom the benefit of adjuvant radiation therapy might be limited. Patients and Methods: We evaluated 411 patients treated with RP from 2001 to 2013 without adjuvant radiation who had an undetectable (<0.01 ng/mL) PSA level after RP but with adverse pathology [positive surgical margins (PSMs), extraprostatic extension (EPE), and/or seminal vesicle invasion (SVI)]. Multivariable Cox regression analyses tested the relationship between pathological characteristics and BCR to identify groups of men at highest risk of early BCR. Results: On multivariable analysis, only pathological Gleason 7 (4 + 3), Gleason ≥8, and SVI independently predicted BCR ( P = 0.019, P < 0.001, and P = 0.001, respectively), although on two‐way analysis men with Gleason 7 (4 + 3) did not have significantly higher rates of BCR compared with patients with Gleason ≤6 (log‐rank, P = 0.074). Men with either Gleason ≥8 (with PSMs or EPE) or SVI (15% of the cohort) defined a high‐risk group vs men without these characteristics (3‐year BCR risk of 50.4% vs 11.9%, log‐rank, P < 0.001). Conclusions: Among men with adverse pathology but an undetectable (<0.01 ng/mL) PSA level after RP, the benefits of adjuvant radiation are probably limited except for men with Gleason 8–10 (with PSMs or EPE) or SVI who are at high‐risk of early BCR.